Hubungan antara Efikasi Diri dan Disposisi Matematis dengan Hasil Belajar - Adi Cahyono Putra; Sulis Janu Hartati; Lusiana Prastiwi (Center of Education Journal (CEJou), 2022)
This research aims to determine the relationship between self-efficacy and mathematical disposition with the mathematics learning outcomes of class X students in Mechanical Engineering at Vocational High School 7 Surabaya. This type of research is correlational research. This research was also an ex post facto study. The population in this study was the tenth grade students of Machining Technique at SMK Negeri 7 Surabaya, the sampling technique in this study was a saturated sample technique. The sample used in this study was 115 students. Data collection on self-efficacy and mathematical disposition was obtained by questionnaire method, while data on mathematics learning outcomes were obtained from mathematical tests. Thedata analysis technique used in this study is multiple correlation analysis with a significance level of 5%. The results in this study indicate that: (1) there is a positive and significant relationship between self-efficacy and mathematics learning outcomes. ; (2) there is a positive and significant relationship between mathematical dispositions and mathematics learning outcomes. ; (3) there is a positive and significant relationship between self-efficacy and mathematical disposition with students' mathematics learning outcomes. Based on the results of the partial correlation test, mathematical disposition variables have more influence on the students' mathematics learning outcomes variables.